DEVELOPMENT OF INTERACTIVE E-MODULES IN RELIGIOUS EDUCATION: A CASE STUDY ON PENDIDIKAN ASWAJA DAN KE-NU-AN - Fitriatin, Nur; Vachruddin, Vrisko Putra; Nabiilah, Zayyin (POTENSIA: Jurnal Kependidikan Islam, 2025)
Driven by the need for a suitable module to facilitate the teaching of Pendidikan Aswaja dan Ke-NU-an subject, we have developed an electronic module (e-module) based on Merdeka Belajar curriculum. This module aims to enhance comprehension, memory retention and empower students to take a more self-directed approach to learning. The aim of Pendidikan Aswaja dan Ke-NU-an as local content subject is to safeguard students from radicalism, extremism, fanaticism and religious intolerance. The research methodology employed in this study is Research and Development (RnD) utilizing the 4D development model comprising four stages: Define, Design, Develop and Disseminate. The e-module incorporates learning outcomes and objectives aligned with Merdeka Belajar curriculum, along with interactive video links connected to the online platform such as YouTube. The results from pilot testing of these interactive e-modules in two sample classes yielded a commendable score of 79%, categorizing it as “fit for use.” The module’s utilization by 67 students across both classes demonstrated significant competency development in knowledge acquisition, comprehension, critical thinking and prevention from radical and extremist viewpoints. This can be seen from affective and cognitive assessments at school. Furthermore, the module effectively addresses epistemological challenges within the field of Aswaja and Ke-NU-an teaching, aligning with the historical evolution of these disciplines and local educational needs.